The Effect of Soybean Powder (Glycine max) to the Histological Structure of Mices (Mus musculus) Liver Cells Induced by Used Cooking Oil - Selvia Anggraeni; Endang Listyaningsih Suparyanti; Ratih Puspita Febrinasari (Nexus Kedokteran Translasional, 2014)
Background: Soybean contain antioxidants which have hepatoprotective effect; one of them is isoflavone. Soybean powder has the highest isoflavone among soybean products. This research aims to prove that the use of soybean powder can prevent damage of the histological structure of the mices liver cells induced by used cooking oil. Methods: This study was an experimental laboratory with a post-test only control group design. Twenty eight Swiss Webster male mice were divided into 4 groups. Negative control group (KN) was given distilled water, the positive control (KP) was given 0.06 ml/ 20 g BW used cooking oil, dose 1 (KD1) was given soybean powder 5.6 mg/ 20 g BW and used cooking oil, and dose 2 (KD2) was given soybean powder 11.2 mg/ 20 g BW and used cooking oil. Soybean powder was given for 14 days, while the used cooking oil was given orally on 8th-14th day. On the 15th day, mice were sacrificed, taken their liver, and made ??preparations with HE staining. Liver cell damage was observed by counting the number of cells with pyknosis, karyorheksis, and karyolysis of 100 cells in liver centrolobular zone. Data were analyzed by statistical tests One-way ANOVA (Analysis of Variant) (? = 0.05). Results: The highest number of liver cells damage is on KP, followed by KD1, KD2, and at least on KN. Results of One-way ANOVA test showed significant differences among the four groups with p = 0.000 (p < 0.05). Results of Post Hoc Test of Multiple Comparasions using LSD test also showed significant differences between KN-KP, KN-KD1, KD2-KN, KP-KD1, KD2-KP, KD1-KD2 with respectively p = 0.000 (p < 0, 05). Conclusion: Soybean powder can prevent damage of the histological structure of the mices liver cells induced by used cooking oil. Keywords: soybean powder, used cooking oil, liver histological structure